Step-by-step explanation:
make sure to number your equations
[tex]2x - y - 3 = 0 \: \: \: \: \: \: \: \: \: \: \: (1)[/tex]
[tex]4x + y - 3 = 0 \: \: \: \: \: \: \: \: \: \: \: \: \: (2)[/tex]
In equation 2 make y the subject
[tex]y = - 4x + 3 \: \: \: \: \: \: \: \: \: (3)[/tex]
subs 3 into 1
[tex]2x - ( - 4x + 3) - 3 = 0[/tex]
[tex]2x + 4x - 3 - 3 = 0[/tex]
[tex]6x - 6 = 0[/tex]
[tex]6x = 6[/tex]
[tex]x = 1 \: \: \: \: \: \: \: \: \: \: \: (4)[/tex]
sub's 4 into 2
[tex]4(1) + y - 3 = 0[/tex]
[tex]4 + y - 3 = 0[/tex]
[tex]y = - 4 + 3[/tex]
[tex]y = - 1[/tex]